Immigrant-Established Resident Interactions in Miami, Florida - Carol Dutton Stepick; Alex Stepick (Studies of Transition States and Societies, 2009)
This article examines factors that affect interethnic relations in Miami, Florida. The theoretical framework, based on the ‘contact hypothesis’ argues that better interethnic relations stem from not only contact, but also contact in which individuals from opposing groups share equal status and a stake in outcomes, and when contact activities require cooperation. The contact hypothesis, however, does not address the factors that produce inequality in social relations. To address these factors ideas from international migration research are used to argue that those with power must create structures in which other groups feel welcome rather than rejected and that leaders must emphasize similarities rather than differences among groups.